Aspirin, nonaspirin nonsteroidal anti-inflammatory drugs, acetaminophen and ovarian cancer survival. Issue 2 (April 2015) - Nagle, Christina M.; Ibiebele, Torukiri I.; DeFazio, Anna; Protani, Melinda M.; Webb, Penelope M.; on behalf of the Australian Ovarian Cancer Study Group
Highlights We have studied, for the first time, associations between aspirin, NSAIDs, acetaminophen and ovarian cancer survival. We investigated use in the 5 years preceding ovarian cancer diagnosis among 1305 women. We found uniformly inverse, but non-significant, hazard ratios for users of aspirin, NSAIDs and acetaminophen. Associations did not differ by histologic subtype or stage at diagnosis. Results provide no strong evidence that use of aspirin or NSAIDs are associated with improved survival.